2013
DOI: 10.1097/bot.0b013e31828c2ad1
|View full text |Cite
|
Sign up to set email alerts
|

Distal Locking Using an Electromagnetic Field–Guided Computer-Based Real-Time System for Orthopaedic Trauma Patients

Abstract: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
1
16
1
1
Order By: Relevance
“…However, extended periods of operation should be considered for misplacement of the distal locking screws. [18] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, extended periods of operation should be considered for misplacement of the distal locking screws. [18] …”
Section: Discussionmentioning
confidence: 99%
“…Compared with the free-hand technique, the electromagnetic technique has a short learning curve for the inexperienced surgeon. Langfitt et al [18] found that junior residents spent more time on inserting the distal screw with the free-hand technique. It is inevitable for the surgeon to receive an excessive dose of radiation, especially for surgeons who do not often perform intramedullary nailing.…”
Section: Discussionmentioning
confidence: 99%
“…However, EM-guided locking SI resulted in a significantly shorter time needed for the procedure and completely eliminated radiation exposure. Langfitt et al [27] compared the efficacy of the two techniques in terms of time and number of interlocking screw misses on 24 tibial nails and 24 femoral nails, which were blocked with 2 distal screws (one by free hand technique and one by electromagnetic fieldguided computer-based real-time system -EFRTS). The results suggest that EFRTS is faster than the traditional freehand technique and results in fewer screw misses.…”
Section: Discussionmentioning
confidence: 99%
“…3 For these reasons, alternate techniques to insert distal locking screws have been proposed, including nail-mounted guides, c omputer navigation, and self-locking nail systems. [4][5][6][7][8][9][10] This evidence pertains to practicing orthopaedic surgeons and residents who have already performed the procedure with fluoroscopic guidance. Compared with conventional fluoroscopic freehand technique, emerging evidence suggests that the use of this device can minimize the number of misses in screw insertion and decrease operative time and radiation dose.…”
Section: Introductionmentioning
confidence: 99%
“…2 Recently, an electromagnetic (EM) targeting device that assists in the insertion of distal locking screws has been introduced (SURESHOT Distal Targeting System; Smith and Nephew, Memphis, TN). [4][5][6][7][8][9][10] There are currently no data examining the use of this technology to teach novice surgical trainees how to perform the procedure-the population of individuals that may have the most difficulty with the freehand technique. [4][5][6][7][8][9][10] This evidence pertains to practicing orthopaedic surgeons and residents who have already performed the procedure with fluoroscopic guidance.…”
Section: Introductionmentioning
confidence: 99%